3PC-023 Development and validation of a discriminative method for anthracyclines used in oncology by visible spectrometer. (24th March 2020) - Adade, CA; El Orche, A; Attjioui, H; Cheikh, A; Mefetah, H; El Karbane, M; Bouatia, M
Abstract : Background and importance: Anthracyclines are among the most used anticancer drugs in haematology–oncology, especially in the treatment of solid tumours and leukaemia. High performance liquid chromatography coupled with spectrometry is a well established method in the control of hospital chemotherapy preparations. However, it remains an expensive method, especially in low income countries. In recent years, UV visible spectrometry associated with partial least square discriminant regression has been used as a method for qualitative and quantitative analysis of drugs in the same therapeutic or physicochemical class. Aim and objectives: The aim of the study was to develop a rapid spectrophotometric method for the discrimination of anthracyclines used in chemotherapy in a paediatric haematology–oncology centre by combining UV visible and partial least square analysis (PLS-DA). Material and methods: Different anthracyclines used routinely (daunorubicin, doxorubicin and epirubicin) were diluted with sodium chloride 0.5% at different concentrations. They were then analysed using a UV vis spectrometer at a wavelength ranging from 300 to 800 nm. Concentrations corresponding to an absorbance of <1 (A <1) were selected for the study. A calibration model was developed by PLS-DA with 25 samples per product. This model was then optimised and validated using three samples per product by projecting them into the space of the latent variables. The statistical software 'the Unscramble X.10.4' performed the chemometric analysis of the data. Results: The model discriminated between the three compounds with a calibration error RMSEC of 0.098 and a regression coefficient of 0.96. Figure 1 shows the factor map of individuals (plot scores) in the 2–3 plane of the PLS-DA result obtained. All validation samples were correctly assigned with 100% accuracy. Conclusion and relevance: This study demonstrated the potential of screw spectrometry associated with the PLS-DA chemometric tool for anthracycline discrimination. It is promising because of its low acquisition cost, speed and ease of use. A calibration range of drug concentrations could allow quantitative control of chemotherapy preparations in the hospital. References and/or acknowledgements: 1. Bazin C, Cassard B, Caudron E, Prognon P, Havard L. Comparative analysis of methods for real-time analytical control of chemotherapies preparations. Int J Pharm 2015;494:329–336. No conflict of interest.